Analysis of an automotive coil spring fracture. (November 2021) - Bergh, Felipe; Silva, Gilmar Cordeiro; Silva, Caio; Paiva, Pedro
Highlights: Analysis of the fracture of an automotive rear suspension coil spring. Root causes of failure determined using laboratory testing procedures. Surface defects generated during poor radial forging acted as stress raisers. Decarburization found inside the defects indicate they were formed before heat treatment. Fatigue cracks that led to the coil spring fracture initiated in the surface defects. Abstract: Failure analysis of a coil spring which failed prematurely during service was carried out using optical and scanning electron microscopy, hardness testing, metallography and optical emission spectroscopy. Indentation marks, which described a helical pattern along the spring wire, were identified in the spring wire below the protective paint. By analyzing the manufacturing process, which included a radial forging stage, it was established that these indentation marks were due to a crack in the forging hammer. One of these marks propagated fatigue cracks, which is confirmed by the presence of ratchet marks on the fracture surface. Observation of a notch at the crack origin, followed by fatigue mechanism and intergranular cracking implies that some sort of stress concentration might have facilitated crack growth and led to failure. It is suggested that radial forging should be carried out by recommended procedures and the status of the forging hammers should be checked before each major run. Careful inspection of the surface after forging must also be carried out to assure product quality and avoid premature failure.